Ontluikende kerke – ‘n nuwe missionêre beweging. Deel 2: Kernpraktyke van Ontluikende Missionêre Kerke - Niemandt, Cornelius J. P. (Verbum et ecclesia, 2008)
This article describes and elaborates on the nine core practices of emerging missional churches, identified in the research of Gibbs and Bolger which presents these practices as innovative answers that can assist mainline churches to discover new possibilities and to change cultural as well as organisational aspects. The article represents a theological reflection on the core practices of emerging churches.